Strategi Pemerintah dalam Pembangunan Infrastruktur Jalan di Kabupaten Jember - Abdul Latib; Achmad Khoiri (JURNAL PARADIGMA MADANI, 2022)
The purpose of this study is to determine the government's strategy in the development of road infrastructure in Jember Regency, especially Jalan MH. Thamrin. The type of research used is descriptive qualitative research, while the data collection techniques used are observation, interviews and documentation. While the informants in this study were 5 people, namely the Head of Highways, Road Development/improvement Section, Road and Bridge Maintenance Section, Traffic Head Office and 3 people/road users. Sources of data used are primary data and secondary data, data analysis techniques with data reduction, data presentation and verification. Validation of the data used is source triangulation, technical triangulation, and time triangulation. The results of the study indicate that the Government's Strategy in Road Infrastructure Development in Jember Regency has not gone well, especially on Jalan MH. Thamrin because in terms of human resources must be further improved or more professional, efficiency and effectiveness have not run optimally because of the constraints that often occur, namely the delayed budget/cost so that the implementation of road construction or maintenance is still not optimal and the roads used are not suitable for use. Keywords: Strategy, Developmen, Road infrastructure